Divalent metal ions modulated strong frustrated M(ii)–Fe(iii)3O (M = Fe, Mn, Mg) chains with metamagnetism only in a mixed valence iron complex. Issue 83 (7th September 2015) - Wu, Qi-Long; Han, Song-De; Wang, Qing-Lun; Zhao, Jiong-Peng; Ma, Feng; Jiang, Xue; Liu, Fu-Chen; Bu, Xian-He
Abstract : Using divalent ions to link the frustrated Fe(iii )3 O units two isostructural chains were generated with distinct magnetic behaviour: frustrations and metamagnetism in mixed valence complex, but magnetic frustrations in heterometallic complexes. Abstract : Linking magnetically frustrated triangular FeIII3O units by divalent metal ions (M II = Fe II for1, Mn II for2 ) gives isostructural 1D spin chains. Strong antiferromagnetic interactions were found in these complexes with significant frustrations but very interesting ferrimagnetic like transition and metamagnetism were found in mixed valence1 . By comparing the magnetic behaviours with isostructural complex 3 (with M II = Mg II ), it is proposed that the spins of Fe II ions and Mn II ions have ferromagnetic and antiferromagnetic contributions respectively.